Pendampingan Program Studi dan Unit Institut Agama Islam Negeri (IAIN) Metro melalui Kegiatan Sistem Audit Mutu Internal (AMI) Berbasis Online - Tusriyanto Tusriyanto; Kisno Kisno; Suryadi Suryadi; Muhammad Mujib Baidhowi; Hotman Hotman; Karsiwan Karsiwan; Sarah Ayu Ramadhani; Fitri Sari (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2022)
The purpose of the higher education quality assurance system is to ensure the fulfillment of higher education standards systemically and sustainably so that a culture of quality grows and develops. Institut Agama Islam Negeri (IAIN) must implement the Internal Quality Assurance System to control and improve the implementation of higher education in a planned and sustainable manner. One of the most important processes of the internal quality assurance system is the evaluation activity carried out through the Internal Quality Audit whose purpose is to see the suitability between the implementation of higher education with higher education standards and standards set by universities. Internal Quality Audit is a form of self-evaluation and as a form of preparation for the internal audit conducted by BAN-PT and other accreditations. Internal Quality Audit activities are carried out by the Quality Assurance Institute of IAIN Metro as the leading sector. The technical implementation is carried out online starting with internal coordination activities, instrument socialization (auditors and auditees) through zoom meetings related to filling out data forms (auditees) and assessment forms (auditors). The scheduled audit implementation is given to each auditor and auditee, the process is carried out through a zoom meeting with the technical room division (breakout room) where each auditee enters the room that has been determined together with the auditor. The results of the auditor's assessment that have been collected at the Quality Assurance Institute were analyzed qualitatively by averaging the results based on the indicators in the assessment instrument. The implementation of the Internal Quality Audit at IAIN Metro online as a whole went well thanks to the cooperation of the entire Quality Assurance Institute team, all institutional leaders as well as auditors and auditees. The implementation of Internal Quality Audit is a fixed price because if it is not carried out every year, it will result in the non-accreditation of all study programs. Keywords: Internal Quality Audit, Auditor, Auditee, online